Students’ Perception of Marriage, Family and Parenthood in the Light of Religious Identity and Religious Tolerance: A Comparative Perspective - Petrović, Jasmina S.; Stjepanović Zaharijevski, Dragana S. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
In a comparative perspective, the paper shows students’ attitudes towards family, marriage and parenthood obtained in an empirical study entitled "Cultural orientation of actors/students, interethnic relations, national identity and the culture of peace in the Balkans" on the samples from the University of Bitola, Veliko Tarnovo and Niš. It analyzes findings from the three subsamples, and tests the hypothesis that students’ religiousness and the firmness of their religious beliefs predicate their attitudes towards family, marriage and parenthood, irrespective of the country where they study. It is expected that the student youth in all subsamples shows preference for the individualistic model of partnership, symmetrical parenting, egalitarian partner and family relationships, but also that the choice of some attitudes clearly indicates the presence of traditional value patterns. At the same time, it is assumed that respondents who identify themselves as firm believers, and those who express a lower level of religious tolerance towards other religions, largely follow traditional patterns in the notion of marriage, family and parenthood. Key words: marriage, family, parenthood, Bitola, Veliko Tarnovo, Nis, students